Functionalized Carbodiimide Mediated Synthesis of 2,3-Disubstituted Quinazolin-4(3H)-ones via the Tandem Strategy of C-Nucleophilic Addition and Intramolecular NH-Substitution Cyclization - Nakano, Hayato; Kutsumura, Noriki; Saito, Takao (Synthesis, 2012)
A facile synthesis of quinazolin-4(3H)-ones possessing carbon substituents at positions 2 and 3 has been developed. Key to the synthesis is a tandem strategy involving introduction of a 2-substituent and construction of the quinazolinone framework via C-nucleophilic addition to the carbodiimide cumulenic carbon followed by intramolecular nucleophilic substitution by the newly formed NH moiety at the proximal ester group.
Keywords: quinazolines; carbodiimides; organometallic reagents; tandem reaction; cyclization